Short-term but not long-term high-fat diet induces an increase in gene expression of gonadotropic hormones and GPR120 in the male mouse pituitary gland - Chikaya DEURA; Ryutaro MORIYAMA (The Journal of Reproduction and Development, 2019)
High-fat diet (HFD) is associated with the regulation of reproductive functions. This study aimed to investigate the effects of short-term HFD on the mRNA expression levels of follicle-stimulating hormone β subunit (FSHβ), luteinizing hormone β subunit (LHβ), gonadotropin-releasing hormone receptor, and long-chain fatty acid receptor, GPR120, in the matured male mouse pituitary gland. Adult male mice were fed either control chow or HFD for 1, 2, 5, 10, 30 and 150 days. Fshb and Gpr120 mRNA expression levels in the pituitary glands were significantly increased during 2 to 30 days of HFD feeding. Gnrh-r mRNA in the 30 days HFD fed group and body weight in the 30 and 150 days HFD fed groups were higher than control. However, there were no significant differences in plasma non-esterified fatty acids or glucose levels during the 150 days of HFD feeding. These results suggest that male mice feeding a short-term HFD induces FSHβ synthesis and GPR120 expression in their pituitary gonadotropes.